INQUÉRITO SôBRE O ESTADO DE NUTRIÇÃO DE UM GRUPO DA POPULAÇÃO DA CIDADE DE SÃO PAULO. IV - Investigação sôbre a ocorrência de deficiência de ácido ascórbico - Gandra, Yaro Ribeiro (Arquivos da Faculdade de Higiene e Saúde Pública da Universidade de São Paulo, 1956)
A study ot clinicai and biochemical examination in order to detect ascorbic acid hypovitaminosis was made in 4208 individuais who considered themselves normal; these individuais c ame to the Health Centers o f São Paulo, accompanying patients. The pathognomonic importancc of the signs and symptoms of the ascorbic acid deficiency is discussed. The incidence of signs and symtoms of this hypovitaminosis was relatively high and is given on Table XXXVIII. The occurence of marginal swollem and red hyperaemic gums was related and a highly significant coefficient of variability of Pearson and a positive and near of one coefficient of Yule were found. One individual from a group similar to ours and with marginal red hyperaemic gums has 89,21% of probability of having swollem gums too. The studies of the relationships between the occurency of gum's signs and perifoliculosis or nervousness gave a coefficient of variability positive and not highly significant. Yule's coefficients were smaller than 0.5 and the probabilities close to 50%.Considering the relationship of skin injuries of the hypovitaminosis C,a highly significant coefficient of variability and also a positive and high Yule's coefficient were found. The probability of one individual with perifoliculosis on the lower limbs to have also violet bruisses in this place is 84,591%. The whole blood concentration of ascorbic acid was detected in 331 individuais of our sample and the results are given on Table XXXIX. Roe and Kuether's technique was employed. 29,3% of the individuais had a rate considered insuficient and 45% hand normal rates. The mean found was 917,2 mg of ascorbic acid per 100 ml of whole blood and the standard deviation 565,68; the standard erro r o f the average was 31,098. Considcrations were made on the interpretation which should be given to blood ascorhic acid concentration if we keep in sight the wide and continuous oscillations to which it is suhjected and which are due, in most cases to dietetic variations. Such dosages were considered by the author as not always translating thc dietetic history of an individual or even of a whole community. The distribution of the results of ascorbic acid concentration expressed by the average of each ten days is given on graphic XV. There was a great variation among thc average of each period. With an additional food survey we have ohscrved that the greater means corresponded to an abundance of mango (ManRifera indica, L.), guava (Psidium pommiferum, L.) and "caquí" (Mimusops Kaki, L.) found in the popular markets. Studies were undertaken to establish the relation between the presence of signs and symptoms of ascorbic acid deficiency and the results of blood concentration of vitamin C. Table XL shows that no relation could be obtained. We could not find any rclationship between the occurrency of anemia and the rate of hlood ascorbic acid. On Table XLI we can see that the greater percentages of anemics are not found among individuais with a low rate of blood ascorbic acid concentration. Considering the relationship among the occurrency of gums signs and pallor of the mucosae or the Iow rates of hemoglobin a non significant coefficient of Pearson and a low coefficient of Yule were found. The values of the prohahilities were very near 50%. Similar results were found in regard to the relationship studies among the occurrency of perifoliculosis of lower limbs and the pallor of mucosae or to the low rates of hemoglobin.